A steady state stoichiometric model describing the anaerobic digestion of biological excess phosphorus removal waste activate sludge - Harding, TH (Department of Civil Engineering, 2014)
A. Background, Principle Objectives and Scope Until the mid-1990's model-based studies on wastewater treatment plants (WWTPs) focussed on the development of models describing a single unit operation within the WWTP i.e. an activated sludge system, an anaerobic digester or some other WWTP unit operation. The focus of these model-based studies changed in the late 1990's due to limitations in linking different models in applications for multi unit operation or full scale plant-wide designs or process evaluations. The boundaries related to the focus of these model-based studies within the WWTP, was widened to develop models that describe more than one unit operation and ultimately the whole WWTP. In line with these plant-wide model-based studies at University of Cape Town an steady state models coupling a primary settling tank (PST) unit coupled to an anaerobic digester (AD) was developed (Sötemann et al., 2005). Furtermore a steady state model coupling an UCT biological excess phosphorus removal (BEPR) activated sludge (AS) system to an aerobic digester was also developed (Mebrutha et al, 2007). Furthermore, the Sötemann et al. (2005) model can also be used to couple the nitrification-denitrification (ND) AS system to an anaerobic digester. To extend the work of these studies, this study focuses on the development of a steady state model that couples an NDBEPR AS system to an anaerobic digester. This study, with the support of a parallel study by Ikumi et al. (2009), aims at developing a steady state AD model that describes the anaerobic digestion of waste activated sludge (WAS) from a NDBEPR AS system and, secondly, comparing the unbiodegradable particulate organic (UPO) fraction determined for the AS and AD systems. The aim (primary objective) of this study was categorised into various secondary objectives to ensure that all aspects related to this study are achieved. The objectives of, and modelling approaches utilized in, this study are largely similar to those reported by Sötemann et al. (2005) in the development of the steady state model describing the anaerobic digestion of primary sludge (PS). Consequently, the steady state AD model of Sötemann et al. (2005) is extended in this study to include the phosphorus and counter-ion metal components contained by NDBEPR WAS. The development of this steady state AD model can be divided into two sections, which are: (a) the characterization of the WAS from the NDBEPR AS system and, (b) the extension and amendment of the Sötemann et al. (2005) steady state AD model to describe the anaerobic digestion of the NDBEPR WAS. ix Each of these sections can then be divided further into secondary sections or parts.